Pengaruh Penggunaan Media Interaktif Kahoot Terhadap Peningkakan Kemampuan Tata Bahasa Arab (Qawaid) - Shilvy Muhda; Syafi’i Syafi’i; suparmanto (The Center for Language Development, Mataram State Islamic University., 2025)
This study investigates how the use of the interactive media Kahoot affects the Arabic grammar skills of students in class X-A at MAN 1 Lamongan in 2025. This study uses a quantitative approach and employs a one-group pretest-posttest design. 26 students, as research subjects, were given multiple-choice tests before and after the treatment. The analysis results show that the average pretest score was 57.3, which increased to 86.5 on the posttest. The t-value of -14.335 with p = 0.000 (< 0.05) indicates a significant difference between the pretest and posttest results. Therefore, Kahoot has a significant effect on students' grammar abilities. The research results show that Kahoot can be an interactive digital learning media alternative that can improve student engagement and learning outcomes in learning Arabic grammar.